Sustainable Stimuli-Responsive Wound Dressing Made of Green Materials - Hummerhielm, Robert (My University, 2022)
Non-healing chronic wound are wound that have a naturally high infection risk and produce an excess of exudate. To better treat these wounds, having a wound dressing that can absorb much of the exudate, keep the wound environment moist, and administer antibiotics when the wound is infected would be ideal. Here, a wound dressing that can absorb large amounts of exudate and locally administer drugs as a response to high pH commonly seen in infected wounds was prepared. First a carboxymethyl cellulose (CMC) aerogel scaffold was first prepared, using ethylene glycol diglycidyl ether (EGDE) as a cross-linker. The scaffold was then impregnated via diffusion or injection with naproxen-loaded pH-sensitive lignin nanoparticles (LNPs), synthesized using an anti-solvent method. Scanning electron microscopy (SEM) was used to investigate the morphology of the CMC gel as well as the shape and size of the synthesized unloaded and naproxen-loaded LNPs. The LNPs efficiency as drug-vehicles was investigated by loading the LNPs with naproxen and calculating the loading capacity and encapsulation efficiency of naproxen. Fourier Transform IR was used to investigate the cross-linking of CMC and EGDE and a tea bag test was used investigate the swelling capacity of the CMC gel. During the synthesis of the CMC gel, several parameters were varied. This resulted in aerogels with different morphologies and properties. Depending on the synthesis parameters, a swelling ratio between 28 and 623 g/g. A high swelling capacity was obtained by adding low concentrations of CMC and EGDE. The lowest swelling capacity was obtained by adding high EGDE concentrations and drying the gel via freeze-drying and oven-drying. Based on the SEM images of LNPs, unloaded and naproxen-loaded LNPs had a desired spherical shape with an average size of 71.6 and 81 nm, respectively. The size distribution was quite large for both LNPs between 31.5–127 nm for unloaded and 26.5–140 nm. The loading capacity of naproxen was around 10% while the encapsulation efficiency was around 48%. Based on the SEM images of the impregnated aerogels, no LNPs could be found. Either no LNPs were present in the sample taken or the LNPs have dissolved due to high pH.
Keywords: wound dressings; carboxymethyl cellulose; aerogel; lignin nanoparticles; drug-loading